Drought-Induced Changes in The Flowering Capacity, Anthesis Quality and Seed Set in Rice (Oryza sativa L.) - Mohd Syahmi Salleh,; Mohd Shukor Nordin,; Adam Puteh,; Rozilawati Shahari,; Zarina Zainuddin,; Mohamad Bahagia Ab-Ghaffar,; Noraziyah Abd Aziz Shamsudin, (Tropical Life Sciences Research, 2022)
Drought stress significantly reduces grain yield (GY) due to poor spikelet fertility and anthesis quality. Aim of this study was to understand the changes of flowering capacity, anthesis quality traits and seed set in the re-watered drought stressed modern high yielding drought susceptible rice cultivar, IR64 at heading (DSH) and booting (DSB) stages. The well-watered plants served as control of the experiment. Results obtained suggest that spikelet moisture content at above 80% was required to maintain optimum anthesis process in rice. Anthesis process in DSH plant was suspended when leaf relative water content (LRWC) dropped to below than 70%. Effects of drought stress on the spikelet moisture were irreversible as compared to the leaf rolling and LRWC. Hence, seed set was failed to occur at the upper rachis branches of the DSH plant. Anthesis process in the re-watered drought stress plants was resumed on the third day after re-watering with about 50% and 80% of anthers managed to dehisce in the DSH and DSB plants. Consequently, percentage of spikelet fertility and seed set in the DSH and DSB plants were increased towards the lower parts of the panicle. The GY, number of seeds, spikelet fertility, and harvest index however were significantly lower in the DSH plant (0.30 g, 13, 16.40% and 14.81) as compared to DSB plant (1.34 g, 57, 59.14% and 48.30), respectively. In addition, all interrelated traits involved in the flowering process of rice could be collectively termed as the anthesis quality traits due to their significant correlation with the grain yield and other yield components.